Neuroimmune Regulation in Sepsis-Associated Encephalopathy: The Interaction Between the Brain and Peripheral Immunity - Liu, Yu-xiao; Yu, Yang; Liu, Jing-peng; Liu, Wen-jia; Cao, Yang; Yan, Run-min; Yao, Yong-ming (Frontiers in Neurology, 2022)
Sepsis-associated encephalopathy (SAE), the most popular cause of coma in the intensive care unit (ICU), is the diffuse cerebral damage caused by the septic challenge. SAE is closely related to high mortality and extended cognitive impairment in patients in septic shock. At present, many studies have demonstrated that SAE might be mainly associated with blood–brain barrier damage, abnormal neurotransmitter secretion, oxidative stress, and neuroimmune dysfunction. Nevertheless, the precise mechanism which initiates SAE and contributes to the long-term cognitive impairment remains largely unknown. Recently, a growing body of evidence has indicated that there is close crosstalk between SAE and peripheral immunity. The excessive migration of peripheral immune cells to the brain, the activation of glia, and resulting dysfunction of the central immune system are the main causes of septic nerve damage. This study reviews the update on the pathogenesis of septic encephalopathy, focusing on the over-activation of immune cells in the central nervous system (CNS) and the “neurocentral–endocrine–immune” networks in the development of SAE, aiming to further understand the potential mechanism of SAE and provide new targets for diagnosis and management of septic complications.